A new Mucocutaneous Activity Index for Behçet's disease - (:unkn) unknown (My University, 2014)
OBJECTIVES: Patient-reported outcomes are increasingly accepted to be major domains in chronic disorders. The aim of this study was to develop a patient-derived disease activity index in Beh-çet's disease (BD). METHODS: One hundred and seventy-seven BD patients (M/F: 69/108) were included in the study. Data were collected by clinical examination and a questionnaire regarding a Mucocutaneous Index (MI) with genital ulcer activity (GI), erythema nodosum activity (EI) and the composite index (CI) for oral ulcers, as subscales of it. Self-reported treatment evaluation was carried out as criterion validity. Patients whose symptoms completely disappeared or decreased significantly, were categorised as 'improved group', others were classified as 'non-improved group'. RESULTS: Among the study group, 79.7% of the patients (n=141) were active, whereas 20.3% were inactive (n=36). Scores of CI, GI, EI and MI score were 0±0 in inactive ones, whereas scores were 5.65±2.36 for CI, 0.81±2.34 for GI, 0.91±2.35 for EI and 6.25±5.1 for MI in actives (p=0.000 for all). MI score was significantly higher in 'non-improved group' (65.5%) compared to 'improved group' (34.5%) (p<0.0001). CONCLUSIONS: The mucocutaneous activity index may help decision-making process for treatment strategies in BD patients.
Keywords: Adult; Female; Humans; Middle Aged; Behcet Syndrome; Cross-Sectional Studies; Male; Skin Ulcer; Severity of Illness Index; Oral Ulcer; Erythema Nodosum